Parallel pattern of differentiation at a genomic island shared between clinal and mosaic hybrid zones in a complex of cryptic seahorse lineages - Riquet, F; Liautard-Haag, C; Woodall, L; Bouza, C; Louisy, P; Hamer, B; Otero-Ferrer, F; Aublanc, P; Béduneau, V; Briard, O; El Ayari, T; Hochscheid, S; et al. (Wiley, 2019)
Diverging semi-isolated lineages either meet in narrow clinal hybrid zones, or have a mosaic distribution associated with environmental variation. Intrinsic reproductive isolation is often emphasized in the former and local adaptation in the latter, although both reduce gene flow between groups. Rarely are these two patterns of spatial distribution reported in the same study system. Here, we report that the long-snouted seahorse Hippocampus guttulatus is subdivided into discrete panmictic entities by both types of hybrid zones. Along the European Atlantic coasts, a northern and a southern lineage meet in the southwest of France where they coexist in sympatry-i.e., in the same geographical zone-with little hybridization. In the Mediterranean Sea, two lineages have a mosaic distribution, associated with lagoon-like and marine habitats. A fifth lineage was identified in the Black Sea. Genetic homogeneity over large spatial scales contrasts with isolation maintained in sympatry or close parapatry at a fine scale. A high variation in locus-specific introgression rates provides additional evidence that partial reproductive isolation must be maintaining the divergence. We find that fixed differences between lagoon and marine populations in the Mediterranean Sea belong to the most differentiated SNPs between the two Atlantic lineages, against the genome-wide pattern of structure that mostly follow geography. These parallel outlier SNPs cluster on a single chromosome-wide island of differentiation. Since Atlantic lineages do not map to lagoon-sea habitat variation, genetic parallelism at the genomic island suggests a shared genetic barrier contributes to reproductive isolation in contrasting contexts-i.e., spatial versus ecological. We discuss how a genomic hotspot of parallel differentiation could have evolved and become associated both with space and with a patchy environment in a single study system.